TRB sequences targeting ORF1a/b are associated with disease severity in hospitalized COVID-19 patients. Issue 1 (13th April 2021) - Assmann, Jorn L J C; Kolijn, P Martijn; Schrijver, Benjamin; van Gammeren, Adriaan J; Loth, Daan W; Ermens, Ton A A M; Dik, Willem A; van der Velden, Vincent H J; Langerak, Anton W
Abstract: The potential protective or pathogenic role of the adaptive immune response to SARS-CoV-2 infection has been vigorously debated. While COVID-19 patients consistently generate a T lymphocyte response to SARS-CoV-2 antigens, evidence of significant immune dysregulation in these patients continues to accumulate. In this study, next generation sequencing of the T cell receptor beta chain (TRB) repertoire was conducted in hospitalized COVID-19 patients to determine if immunogenetic differences of the TRB repertoire contribute to disease course severity. Clustering of highly similar TRB CDR3 amino acid sequences across COVID-19 patients yielded 781 shared TRB sequences. The TRB sequences were then filtered for known associations with common diseases such as EBV and CMV. The remaining sequences were cross-referenced to a publicly accessible dataset that mapped COVID-19 specific TCRs to the SARS-CoV-2 genome. We identified 158 SARS-CoV-2 specific TRB sequences belonging to 134 clusters in our COVID-19 patients. Next, we investigated 113 SARS-CoV-2 specific clusters binding only one peptide target in relation to disease course. Distinct skewing of SARS-CoV-2 specific TRB sequences toward the nonstructural proteins (NSPs) encoded within ORF1a/b of the SARS-CoV-2 genome was observed in clusters associated with critical disease course when compared to COVID-19 clusters associated with a severe disease course. These data imply that T-lymphocyte reactivity towards peptides from NSPs of SARS-CoV-2 may not constitute an effective adaptive immune response and thus may negatively affect disease severity. Graphical Abstract: The T cell receptor beta chain (TRB) repertoire of hospitalized COVID-19 patients revealed that TRB sequences targeting nonstructural proteins of SARS-CoV-2 may negatively affect disease severity.